How Do Farmers Learn from Extension Services? Evidence from Malawi. Issue 2 (18th September 2020) - Maertens, Annemie; Michelson, Hope; Nourani, Vesall
Abstract : Though extension services have long since proved their value to agricultural production and farmer prosperity, their record in sub‐Saharan Africa has been mixed. To study the impact of such programs on farmers' learning about agricultural technologies, we implemented a quasi‐randomized controlled trial and collected detailed panel data among Malawian farmers. Based on those findings, we develop a two‐stage learning framework, in which farmers formulate yield expectations before deciding on how much effort to invest in learning about these processes. Using data centered on farmer beliefs, knowledge, and constraints, we find evidence that beliefs about potential yields hinge on first‐hand and local experience, and that these beliefs significantly impact learning efforts. Consistent with this, we find that farmers who participated in season‐long, farmer‐led demonstration plot cultivation plan to adopt more components of new multi‐component technology, compared to farmers who were invited to attend only field‐day events.